Development of an architecture-property model for triply periodic minimal surface structures and validation using material extrusion additive manufacturing with polyetheretherketone (PEEK). (September 2022) - Spece, Hannah; DeSantis, Paul M.; Kurtz, Steven M.
Abstract: Additively manufactured structures designed from triply periodic minimal surfaces (TPMSs) have been receiving attention for their potential uses in the medical, aerospace, and automobile industries. Understanding how these complex geometries can be designed to achieve particular architectural and mechanical properties is essential for tuning their function to certain applications. In this study, we created design tools for visualizing the interplay between TPMS design parameters and resulting architecture and aimed to validate a model of the relationship between structure architecture and Young's modulus. A custom MATLAB script was written to analyze structural properties for families of Schoen gyroid and Schwarz diamond structures, and a numerical homogenization scheme was performed to predict the effective Young's moduli of the structures based on their architecture. Our modeling methods were validated experimentally with polyetheretherketone (PEEK) structures created using material extrusion additive manufacturing. The architectural characteristics of the structures were determined using micro-computed tomography, and compression testing was performed to determine yield strength and Young's modulus. Two different initial build orientations were tested to determine the behavior both perpendicular and parallel to the layer deposition direction (referred to as z-direction and xy-direction, respectively). The z-direction Young's modulus ranged from 289.7 to 557.5 MPa and yield strength ranged from 10.12 to 20.3 MPa. For the xy-direction, Young's modulus ranged from 133.8 to 416.4 MPa and yield strength ranged from 3.8 to 12.2 MPa. For each initial build orientation, the mechanical properties were found to decrease with increasing porosity, and failure occurred due to both strut bending and interlayer debonding. The mechanical properties predicted by the modeling agreed with the values found for z-direction samples (difference 2–11%) but less so for xy-direction samples (difference 27–62%) due to weak interlayer bonding and print path irregularities. Ultimately, the findings presented here provide better understanding of the range of properties achievable for additive manufacturing of PEEK and encouraging results for a TPMS architecture-property model.